REINTRODUCING THE IMPORTANCE OF TEACHING ENGLISH AT PRIMARY SCHOOLS IN INDONESIA - Istiqomah, Faizatul (Pusat Pengembangan Bahasa, 2016)
There has been a long debate about children learning a foreign or second language (SL) at an early age. Some claim that learning a foreign language (FL) can burden children who are still struggling in mastering their native language (NL). In case of Indonesian context, English has been excluded from the 2013 curriculum. Arguments supporting the elimination seem baseless and worth revising. Considering the benefits of learning English which outweigh the drawbacks in terms of improving the quality of the next generation, Indonesian government should recommend English to be taught in elementary schools. Some important points regarding human or teachers and teaching resources need to be taken into account further.